(untitled) (Bangladesh Journal of Medicine, 2022)
Background: COVID-19 vaccines have a high rate of success in averting hospitalization and mortality. However, COVID-19 infection is still being detected among immunized patients, although with blunted severity. This study aimed to compare the severity and outcome of COVID-19 among immunized versus non-immunized individuals. Methods: This cross-sectional study was conducted over 179 COVID-19 patients in Popular Medical College Hospital, Dhaka. All the methods in the present study were carried out following the ethical guidelines of the 1975 Declaration of Helsinki. Data were collected from both hospital record and direct interview. Data were recorded in separated case record form and analyzed by STATA version 14. Results: Mean age of the study patients was 55.42±14.20 (SD) years wherein maximum were male (61.5%). Fever (88.8%), cough (81.6%), dyspnea (47.5%) and sore throat (30.2%) were most common symptoms. Maximum patients werehypertensive (60.9%) and diabetic (58.7%). About 35.8% of patients had mild severity, while 27.9% had moderate, 23.4% had severe, and 12.8% had critical stage. Maximum patients (n=122, 68.2%) were nonvaccinated and rest (n=57, 31.8%) had received 1st dose of vaccine. Vaccinated patients had significantly higher frequency of having mild COVID-19 (57.9% vs 31.1%, p<0.001) and getting discharge with full recovery (94.7% vs 76.2%, p=0.003) compared to non-vaccinated patients. Moreover, non-vaccinated patients were more prone to develop critical clinical syndrome (10.6% vs 1.8%, p=0.039) and had died or referred to higher center (11.4% vs 1.8%, p=0.029) than vaccinated individuals. Conclusion: COVID-19 vaccination was significantly associated with mild severity and lower rate of adverse outcome. Bangladesh J Medicine 2022; 33: 293-299